Data-Driven Social Marketing for Health Education: Predicting Low-Sugar Consumption Intentions with HBM and TPB among Indonesian University Students - Haidar Ali, Mohammad; Amer, Afizan (Corolla International Conference, 2025)
This study investigates determinants of university students’ intentions to shift from high-sugar to low-sugar products in Indonesia using an integrated Health Belief Model (HBM) and Theory of Planned Behavior (TPB) framework. Excessive sugar intake is a global health concern linked to obesity, type 2 diabetes, and other non-communicable diseases, and Indonesia is projected to face a sharp increase in diabetes prevalence by 2045. A cross-sectional explanatory survey of 150 Hasyim Asy’ari University students was conducted using stratified random sampling and a structured Likert-scale questionnaire measuring perceived benefits, perceived barriers, attitude, perceived behavioral control, subjective norm, and intention. Data were analyzed with PLS-SEM. All constructs met reliability and validity criteria, and the model explained 54.9% of the variance in attitude and 65.5% in intention. Attitude was the strongest predictor of low-sugar consumption intention, reinforced by perceived benefits and weakened by perceived barriers, while perceived behavioral control also significantly increased intention; subjective norm was not significant. The findings validate the applicability of the integrated HBM–TPB model for healthy consumption behavior in a developing-country context and offer evidence-based directions for social marketing and campus health interventions targeting low-sugar choices among Generation Z students.